Correlations between age of Bali bull and semen production at National Artificial Insemination Center, Singosari - Indonesia - Nugraha, C. D.; Herwijanti, E.; Novianti, I.; Furqon, A.; Septian, W. A.; Busono, W.; Suyadi, S. (Diponegoro University, 2019)
The aim of this research was to analyze the correlation of age of Bali bull to the body weight and semen qualities. The materials were 50 Balibulls data collected from 2012 to 2018. Therecordeddatawere consisted ofsemen productions (n = 1304) and body weight (n = 1544). The observation was conducted to analysis the interrelationship between the Bali bulls age and body weight (BW), to the semen volume (SV), individual motility (IM) and sperm concentration (SC). The obtained data was analyzed with One-Way ANOVA analysisby using SPSS 24 and followed with Duncan’s Multiple Range Test to determine any significant differences. The correlation between Bali bulls age (the independent variable) and semen quality (the dependent variable) was computed by using Pearson correlation method and presented in linear regression models. The results showed that the Bali bulls agesignificantly affect (P<0.05) the BW from the age of 1 to 10 years old. The age also showed a significant effect (P<0.05) on the semen qualities. The age correlated significantly (P<0.05) with BW, SV, IM, SC were 0.658, 0.386, 0.134 and 0.086, respectively. Inconclusion,the age of Bali bull could be used as an indicator todetermineits BWand semenqualities.